Pre-licensure medical students’ knowledge and views on interprofessional learning: A qualitative concept analysis based on real-world data - Berger-Estilita, Joana; Merlo, Sofia; Guttormsen, Sissel; Fuchs, Alexander; Greif, Robert; Chiang, Hsin (Frontiers in Education, 2022)
Background The several definitions of Interprofessional Education (IPE) allow for different interpretations and interchangeable terms. This study aims to determine the characteristics and attributes of the definition of IPE. Materials and methods In November 2019, 31 medical students (64.5% female) from a single institution took part in nine semi-structured interviews. We created a deductive three-level code system followed by an inductive code system based on several known IPE definitions. We extracted the main entities of the concept of IPE according to both code systems to create a framework. We used MaxQDA software for qualitative analysis. Verification of codes and categories was attained through sequential peer-debrief. Results Participants correctly named the WHO’s definition of IPE, and outlined its four main dimensions according to the Interprofessional Education Collaborative report. We found new IPE attributes and demonstrated the weight of communication and role recognition. Two-thirds of medical students mentioned IPE activities that we classified as a contrary model (without collaboration or patient-centeredness) and a minimum weight was given to the importance of patient-centeredness. Conclusion Medical students’ understanding of the concept of IPE is coherent. We deepened the understanding of previously identified definitions of IPE, and we identified new attributes of the concept. Finally, we added “well-being” as a component of interprofessionality. Clinical Trial Registration [https://www.isrctn.com/], identifier [ISRCTN41715934].